Penerapan Standar Akuntansi Keuangan Entitas Mikro Kecil Menengah (SAK EMKM) pada Umkm di Kota Padang - Lisa Fitriani Rahman Shinta Ayudhi (Jurnal Kajian Akuntansi dan Auditing, 2020)
This study aims to see to find out the application of SAK EMKM to MSMEs in Padang Barat District. To determine the effect of applying the EMKM to MSMEs for the growth of MSMEs in Padang Barat District.The sample in this study was obtained from the Office of Cooperatives and Small and Medium Enterprises for West Padang Subdistrict as many as 171 samples using the Slovin formula. The application of financial accounting standards for small and medium micro entities (SAK EMKM) has a positive and significant influence on the growth of small and medium micro enterprises because the significance value obtained is 0,000 < 0,05 which is supported by the value of t count of 14,633 > t table of 1,973. The magnitude of the ability of the independent variable in this case is the application of the small and medium micro financial entity accounting standard (SAK EMKM) to the dependent variable in this case is the growth of small and medium micro enterprises by 55.90% while the remaining 44.10% is influenced by variables other than variables that were not included in the research model